The Impact of Students’ Stream from Secondary School on the Development of Critical Thinking at the Tertiary level - LAKRID, Houaria (My University, 2017)
The present study attempts to investigate the learners’ critical thinking at university. It examines the role of streams from secondary school on the development of critical thinking as being regarded as an essential competence. In which skills of questioning, analyzing, synthesizing, etc are encouraged. It aims at finding whether the teaching practices at secondary schools are supported with activities that are disposed to enhance critical thinking. And if this latter is developed at secondary school, which stream is responsible for that achievement. Furthermore, it examines what critical thinking is; its characteristics; and its importance to learners. Hence, three hypotheses were presented in this paper. However, to test these hypotheses two data means are presented: a questionnaire was answered by students from master two, the specialty of Didactics and Applied linguistics at Mostaganem University. Besides and interview was done with some of students from the same group. On the basis of the results, the teaching practices in Foreign Languages stream include tasks that enhance critical thinking, but not that much since most students from that stream agree that they developed their critical thinking at university. Whereas, students that belong to the other streams assumed that they do not consider themselves as critical thinkers since their teachers were focusing on linguistic competences and grammar lessons. The rest of them who said they think critically, they said they developed it at university even though they lack motivation because it was not their choice to be at English Department. Therefore, serious changes should be done to help learners think critically in secondary school, so that when they pass to university it will not be an issue to think critically in learning a foreign language.
The Case of Second Year Master Students, Didactics and Applied Linguistics
Keywords: Critical Thinking; Skills, Development; Secondary School; Streams; Tertiary level